Optimalisasi Pengelolaan Persediaan Melalui Sistem Informasi Akuntansi Berbasis SAP ERP - Bagus Brasilio; Driana Leniwati (Value : Jurnal Manajemen dan Akuntansi, 2026)
The development of information technology has encouraged the transformation of inventory management to be more integrated and data-based, but there are problems such as dead stock and high inventory elimination costs still occur in the port sector. This study aims to analyze the application of SAP ERP-based Accounting Information System in minimizing the cost of inventory elimination and identifying obstacles and implementation opportunities at PT Terminal Petikemas Surabaya. The research uses an interpretive qualitative approach with a case study design. Data were obtained through in-depth interviews with six expert informants from the Planning and Inventory, Accounting, and Procurement Divisions, supported by observation, documentation, and literature studies. Data analysis was carried out using thematic analysis through the process of transcription, coding, categorization, theme determination, and triangulation. The results show that the implementation of SAP ERP improves the accuracy of stock data, integrates information between divisions, and accelerates the identification of slow-moving inventory and inventory aging, thus contributing to a reduction in the cost of inventory clearance. Internal documentation shows a decrease in the value of write-off inventory by about 28% after SAP ERP implementation. System optimization has not been fully achieved due to limited user competence, delays in data updates, lack of optimal use of analytics features, and managerial decisions that are not fully based on system indicators. These findings show that SAP ERP plays an enabler in improving the effectiveness of inventory management, with its success being influenced by the alignment between technology, human resources, and organizational governance.